(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
Water is a vital resource for life that cannot be dispensed with, for humans and other creatures in the entire ecosystem. However, these water resources are characterized by an unequal distribution, in addition to their mobile nature and their penetration of geographical boundaries, rendering them a shared resource for all humanity, whether within the borders of a single state or among the peoples of multiple states. The inter connected nature of transboundary waters also imposes cooperation on the concerned states for their optimal utilization and management, especially in light of scarcity and increasing competition among states to meet their diverse and growing needs, and to meet developmental needs for each state individually. Therefore, the issue of water is not only related to its quality or abundance, or the risks arising from it, but it is a problem with multiple dimensions: environmental, social, economic, and legal, especially concerning transboundary water resources. The Renaissance Dam has become a critical challenge for the Nile Basin’s riparian countries. The Nile Basin, one of the most complex and distinctive river basins, is characterized by its vast expanse, varied climate, and topography. This diversity creates significant obstacles to managing the basin’s transboundary water resources effectively.